2022
DOI: 10.1039/d1fo03241k
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of a high-fat diet combined with dietary advanced glycation end products on cognitive function and protection with voluntary exercise

Abstract: To determine whether high fat diet (HFD) combined with advanced glycation end products (AGEs) diet will induce worse cognitive impairment than HFD per se, and whether voluntary exercise is capable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Allobaculum , which is involved in butyric acid production [ 48 , 49 ], increases following the consumption of a high fat diet in rodents that produces cognitive impairments [ 38 , 50 , 51 ]. While this suggest that increased levels of Allobaculum may be related to suboptimal health, other studies have reported that voluntary exercise can lead to enhanced abundance of Allobaculum [ 52 , 53 ]. Thus, future studies should attempt to manipulate Allobaculum abundance directly to examine the impact on cognitive function and metabolic health.…”
Section: Discussionmentioning
confidence: 98%
“…Allobaculum , which is involved in butyric acid production [ 48 , 49 ], increases following the consumption of a high fat diet in rodents that produces cognitive impairments [ 38 , 50 , 51 ]. While this suggest that increased levels of Allobaculum may be related to suboptimal health, other studies have reported that voluntary exercise can lead to enhanced abundance of Allobaculum [ 52 , 53 ]. Thus, future studies should attempt to manipulate Allobaculum abundance directly to examine the impact on cognitive function and metabolic health.…”
Section: Discussionmentioning
confidence: 98%
“…Our results show that several of these SCFA-producing families allow performance prediction according to the GEE models, such as Coriobacteriaceae and Bifidobacteriaceae , from PC1, Erysipelotrichaceae from PC2, and Sutterellaceae from PC3. These families have previously been described as associated with improved physical performance and exercise-related health status in mouse and human studies [ 27 , 28 ]. Thus, Coriobacteriaceae abundance has been described as a biomarker linking physical exercise with improved health status, probably via diverse catabolic pathways, such as secondary bile acids and aldosterone 18-glucuronide metabolism, involved in sodium homeostasis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, most studies used heat‐treated foods for feeding mice to study the effects of dietary AGEs intake on organismal health (Luo, Li, et al, 2022; Roncero‐Ramos et al, 2013). However, extensive heat processing foods contain various antinutritional and toxic compounds derived from the Maillard reaction (e.g., acrylamide [Quan et al, 2022], heterocyclic aromatic amines [Dong et al, 2020], and 5‐hydroxymethylfurfural [Han et al, 2019; Pérez‐Burillo et al, 2019]).…”
Section: Introductionmentioning
confidence: 99%